The Impact of Formative Assessment on the Learning Process and the Unreliability of the Mark for the Summative Evaluation. (25th July 2015) - Tridane, Malika; Belaaouad, Said; Benmokhtar, Said; Gourja, Bouchra; Radid, Mohamed
Abstract: In this work, we highlight the impact of formative assessment on the learning and the unreliability of the mark for the summative evaluation process. To achieve this study, we distributed to 250 students of the common core sciences, a questionnaire to the representations of the students acquired during their learning situations. The questionnaire covers the main concepts of the courses that have been taught, namely, electric current; electric voltage; quantity of material and molar concentration. After collecting all the answers to the questionnaire, we corrected them. We looked through the summative evaluation for the acquisition of concepts by students and the effect of adjustment of representations on their marks. We put in question the reliability of the marks that we can allocate. Therefore, we distributed photocopies of 50 copies before their correction to 20 secondary school teachers, in order to have more information on systematic errors of the marks, their limit and their reliability. On the light of these results, we can say: - Formative assessment can help teachers to anticipate in advance treating the gaps of the students and changing these methods, if necessary, in the learning process. - Summative assessment may not reflect the level of acquisition of the taught concepts. Therefore, the revision of assessment methods of the concepts among learners is required. These evaluation methods are unable to properly assess the level of acquisitions of students, as they differ from one teacher to another.